THE ROLE OF ECONOMIC EDUCATION IN BUILDING FINANCIAL INDEPENDENCE AMONG YOUTH - Pramesthi, Yunesia (Berajah Journal, 2024)
This study examines the significant role of economic education in fostering financial independence among youth. In an era where financial literacy is critical for personal and societal well-being, integrating economic education into school curricula is essential. This article highlights the importance of equipping young individuals with the necessary skills to make informed financial decisions. The research outlines the theoretical framework underpinning financial independence, the impact of economic education on youth, and various teaching methodologies that enhance learning outcomes. Furthermore, it addresses the challenges educators face in implementing effective economic education programs and proposes strategies for overcoming these obstacles. The findings suggest that comprehensive economic education can lead to improved financial behaviors, increased savings, and better decision-making skills among young individuals. Ultimately, this study emphasizes the need for educational institutions to prioritize economic education to prepare youth for a financially independent future.